2022
DOI: 10.3389/fendo.2022.973058
|View full text |Cite
|
Sign up to set email alerts
|

The role of protein kinase C in diabetic microvascular complications

Abstract: Protein kinase C (PKC) is a family of serine/threonine protein kinases, the activation of which plays an important role in the development of diabetic microvascular complications. The activation of PKC under high-glucose conditions stimulates redox reactions and leads to an accumulation of redox stress. As a result, various types of cells in the microvasculature are influenced, leading to changes in blood flow, microvascular permeability, extracellular matrix accumulation, basement thickening and angiogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 127 publications
0
22
0
Order By: Relevance
“…PKC is a member of the serine/threonine kinase family and can be classified into three subgroups, including classical/conventional PKCs (cPKCs), novel PKCs (nPKCs), and atypical PKCs (aPKCs), depending on the mode of activation [ 41 ]. As a commonly expressed enzyme, different PKC isoforms are activated during the progression of diseases in different tissues and organs [ 42 ].…”
Section: The Pathological Process Of Dusmentioning
confidence: 99%
“…PKC is a member of the serine/threonine kinase family and can be classified into three subgroups, including classical/conventional PKCs (cPKCs), novel PKCs (nPKCs), and atypical PKCs (aPKCs), depending on the mode of activation [ 41 ]. As a commonly expressed enzyme, different PKC isoforms are activated during the progression of diseases in different tissues and organs [ 42 ].…”
Section: The Pathological Process Of Dusmentioning
confidence: 99%
“…[40] In DM, the PKC are triggered by AGEs, oxidants, such as H 2 O 2 , mitochondrial superoxide and DAG due to the intracellular hyperglycemia. [41][42][43][44] Hyperglycemic condition plays a great role in inhibition of glyceraldehyde-3-phosphate dehydrogenase which further leads to the accumulation of glyceraldehydes-3-phosphate. [24] Then, the level of dihydroxyacetone-3-phosphate (DHA-3-P), a triose isomer of the glyceraldehydes-3-phosphate (G-3-P), will be elevated.…”
Section: Protein Kinase C Pathwaymentioning
confidence: 99%
“…[78] The process of fracture healing consists of 3 well-defined stages: inflammatory, bone regrowth, and remodeling, and all these phases are affected in patients with DM. [44] In addition to affecting fracture healing, patients with T2DM have higher relative risks for fractures compared to the patients without T2DM. [79] A recent study has showed that patients with T2DM were significantly frailer than individuals without diabetes [61] 38(50%) distal radius and tibia Higher cortical porosity Higher trabecular volumetric BMD and trabecular thickness A Shu et al ( 2012) [62] 50(50%) tibia lower cortical area Janina M Patsch et al ( 2013) [63] 80(50%) ultradistal and distal radius and tibia Higher cortical porosity at radius Lower cortical porosity at tibia E W Yu et al (2014) [64] 100(22%) distal radius and tibia Lower cortical vBMD and tissue mineral density Joshua N Farr et al (2014) [66] 60(50%) distal radius and tibia Higher radial cortical porosity Julien Paccou et al ( 2016) [67] 332(9%) distal radius and tibia Higher cortical pore volume at the distal radius Higher cortical pore volume and cortical porosity at the distal tibia U Heilmeier et al ( 2016) [68] 80(50%) distal tibia and radius Higher global porosity Higher porosity in the midcortical and periosteal layers Vikram V Shanbhogue et al ( 2016) [69] 51(50%) distal radius and tibia Lower cortical volumetric BMD and cortical thickness and higher cortical porosity at the radius Higher cortical porosity at the tibia Anna G Nilsson et al ( 2017) [70] 1053 (9%) ultradistal and distal radius and tibia Higher trabecular bone volume fraction, distal cortical volumetric BMD and cortical area Lower cortical porosity in the distal radius Janina M Patsch et al (2017) [71] 85(50%) ultradistal radius and tibia Higher cortical thickness at the radius Higher trabecular hypertrophy and trabecular number Jessica F Starr et al ( 2018) [72] 92(46%) distal radius and tibia Higher plate-like and lower rod-like trabecular network Elizabeth J Samelson et al ( 2018) [73] 1069(12%) distal radius and tibia Lower cortical volumetric BMD and higher cortical porosity at the tibia E A C de Waard et al (2018) [74] 344 (19%) distal radius and tibia Lower cortical vBMD, cortical thickness, higher cortical porosity and trabecular number of the radius Higher trabecular number and lower trabecular thickness of the tibia Ursula Heilmeier et al (2021)…”
Section: T2dm and Bone Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial dysfunction is signified by the prevalence of oxidative stress, an event which occurs in response to hyperglycemic damage (18)(19)(20). In DCM, various pathways are activated in response to oxidative stress, resulting in altered signaling, and increasing the expression of VEGF, TGFβ, and NF-κB, collagen and fibronectin independent of fibroblasts (6,(21)(22)(23)(24)(25)(26). TGF-beta and NF-κB further promote the differentiation of fibroblasts to myofibroblasts (27,28).…”
Section: Introductionmentioning
confidence: 99%